Concentration assessment of interleukin 8 in serum at children with uveitis - Żelazowska-Rutkowska, Beata; Mrugacz, Małgorzata; Wysocka, Jolanta; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Uveitis in children is a visual threatening disease with a complication rate of more than 75%. At the children the uveitis differs in several aspect from adults like: clinical presentation or complication of disease. The etiology of uveitis is still unknown, but T lymphocytes are generally key mediators of the pathogenesis of uveitis. In our study we evaluate IL-8 concentration in serum in uveitis patients. Material and methods: Serum sample were collected from 28 uveitis patients and 20 people from control group. The level of IL-8 was measured with specific enzyme- linked immunoassays ELISA methods (R & D Systems). Results: Level of IL-8 in uveitis group was a significant higher (p<0.04) compared with control group. Conclusions: Increased levels of interleukin 8 in serum of children with uveitis may suggest innate immune mechanisms in the acute disease.